New horizons in piling : development and application of press-in piling - Bolton, Malcolm; Kitamura, Akio; Kusakabe, Osamu; Terashi, Masaaki (Boca Raton : CRC Press, 2021)
The piling industry has, in recent years, developed a variety of press-in piling technologies with a view to mitigate noise & vibration nuisance. This book focuses on the "Walk-on-Pile" type press-in piling system, which offers an alternative engineering solution for piling works. This type of piling has unique features, including the application of the compact piling machine using pre-installed piles as a source of reaction force to jack in a new pile by hydraulic pressure. Moreover, the machine can walk along the top of piles already installed, thus enabling piling in a limited space and headroom with minimum disruption to social functions and services of existing infrastructure. These features are opening up a new horizon in piling, leading to novel application of embedded walls previously considered impossible. This introductory book provides a historical development of press-in piling and various challenging applications worldwide as well as scientific research outcomes, forming a valuable source of reference for readers who are unfamiliar with press-in piling, including project owners, design engineers, practical engineers as well as researchers and students.
OCLC-licensed vendor bibliographic record.
Keywords: Piling (Civil engineering); TECHNOLOGY / Engineering / Civil